2, 4-Dinitrofenilhidrazonas de ß-halocetoesteres alilicos - Sánchez, Oscar (1990)
Conventional methods for forming 2, 4-dinitrophenylhydrazones usually leave traces of acids complexed with derivatives and cause variable melting points. NMR studies showed that traces of acids catalyse the syn-anti isomerization or dehydration of the products and thus cause the melting point anomalies. In recent years anention has been directed to the use of other solvents in which the reagent as the free base is more soluble and which therefore do not require the high acid concentration used in earlier procedures.